The Mediating Role of Mindfulness in the Relationship Between Metacognitive Beliefs and Wisdom in Students - Shoghi, Behzad; Behzadafshar, Tayyebeh (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to investigate the mediating role of mindfulness in the relationship between metacognitive beliefs and wisdom among students. Methodology: The research methodology was applied in terms of its purpose and descriptive-correlational in terms of data collection method. The population of this study consisted of all students of the Free Universities of Tehran Province in the academic year 2021-2022, among whom 380 individuals were selected through multi-stage cluster sampling. In this research, Ardelt's Wisdom Questionnaire (2003), Wells' Metacognitive Beliefs (2000), and Ryan and Brown's Mindfulness (2003) were used, all of which had acceptable reliability and validity. Structural equation modeling with SPSS-V23 and Lisrel-V8.8 software was used for data analysis and to address the research hypotheses. Findings: The findings showed that mindfulness directly affects wisdom (t = 11.57, β = 0.28); metacognitive beliefs directly affect mindfulness (t = 11.82, β = 0.38); metacognitive beliefs directly affect wisdom (t = 11.81, β = 0.37); and the total effect of metacognitive beliefs on wisdom through the mediation of mindfulness was significant (β = 0.49). Conclusion: Ultimately, it can be said that the research model also had a suitable fit. In general, it can be stated that with the increase in metacognitive beliefs and mindfulness variables, an increase in wisdom among students can be expected.